Factors Related to Compliance With The Use of Personal Protective Equipment (PPE) Cleaning Service Officer at Morowali Hospital - Subeo, Nurafni; Miswan; Rismawati, Nur (Yayasan Sinergi Kawula Muda, 2025)
Non-medical personnel who have the potential to contract occupational diseases are officers cleaning service. Risks that may be faced by officers cleaning service namely being exposed to chemicals, being pricked by sharp objects such as syringes when throwing away rubbish. Implementing compliance with the use of PPE is important to protect officers from work safety hazards. The aim of this research is to determine the factors related to compliance with the use of personal protective equipment among officers cleaning service at Morowali Regional Hospital. This research method is a type of quantitative research. Research design used cross sectional. Sampling was carried out using total sampling with a total of 38 respondents. Results of work period research on compliance with the use of personal protective equipment in cleaning service P value=0.235>0.05, while monitoring and compliance with the use of PPE P value= 0.013<0.05. As well as perceptions regarding compliance with the use of PPE with test results chi-square with P value= 0.015<0,05. There is no relationship between length of service and compliance with the use of PPE. Meanwhile, monitoring and perception results show that there is a relationship with compliance with the use of PPE cleaning service. It is recommended that agencies increase supervision and provide sanctions or punishments that can have a deterrent effect on officers who do not use PPE when working, carry out inspections and advise companies to prioritize the safety of each officer. cleaning service.